Implementation of Cooperative Learning Model Towards Improving Writing Competence Student Argumentation Discourse Text Class XI State Vocational School 1 Lolofitu West Nias - Zebua, Septinus; Sutikno (International Journal of Educational Research Excellence (IJERE), 2025)
This study aimed to(1). To determine students' ability to write argumentative discourse before being taught using the cooperative learning model; (2). To determine students' ability to write argumentative discourse after being taught using the cooperative learning model (3). to determine whether the application of the cooperative learning model has a significant influence on students’ ability to write argumentative discourse in class. The population in this study was a class. The sample consisted of 30 Xi students. This study used an experimental method with a test instrument for the ability to write argumentative discourse. This test was tested 2 (two) times, namely, pretest and posttest. After each sample took the pretest, they were given treatment using the cooperative learning model, then given another test (posttest), and the scores were compared with each other. Comparative analysis uses the "t" test. Based on the data analysis techniques, it can be concluded that the pretest results, namely before the cooperative learning treatment, had an average score of 63.3, which is still low. Furthermore, the post-test results of students who were taught using the cooperative learning model received a high average score of 79.2. This shows that the use of the cooperative learning model has a significant influence on improving the ability to write argumentative discourse by class XI students at SMK Negeri 1 Lolofitu, West Nias Regency, Academic Year 2024-2025